2021
DOI: 10.1088/1757-899x/1041/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Occupational Noise Exposure to Work-Fatigue of Indonesian Crumb Rubber Plants

Abstract: The purpose of this research was to analyze the effect of noise on the level of work-fatigue in the production area of three crumb rubber plants at Padang City, Indonesia. It also examines the impact of age, period work, marital status, and education level on work-fatigue. Occupational noise in the working area was measured using a Sound Level Meter, while work-fatigue was measured using the Indonesian fatigue measurement questionnaire (KAPUK2). The respondents of this study were workers in these plants, 213 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“… 29 Physical workload combined with noise intensity that exceeds 85 dB(A) for 8 hours of work could lead to fatigue symptomps such reduced concentration, physical exhaustion, dizziness and others. 30 , 31 Yovi et al 21 stated that noisy environmental conditions can cause the operator to feel tired and lose their concentration easily. Therefore, one strategy to control noise exposure is for the company to provide replacement workers when the noise exposure has exceeds the allowed time limit and provide them with the necessary PPE.…”
Section: Resultsmentioning
confidence: 99%
“… 29 Physical workload combined with noise intensity that exceeds 85 dB(A) for 8 hours of work could lead to fatigue symptomps such reduced concentration, physical exhaustion, dizziness and others. 30 , 31 Yovi et al 21 stated that noisy environmental conditions can cause the operator to feel tired and lose their concentration easily. Therefore, one strategy to control noise exposure is for the company to provide replacement workers when the noise exposure has exceeds the allowed time limit and provide them with the necessary PPE.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of 348 workers at a crumb rubber factory in Padang, Indonesia, a correlation was found between noise exposure and work fatigue (t = 2.024; p = 0.046 < 0.05). The results showed that 26.19% of the workers experienced mild fatigue, 71.43% experienced moderate fatigue, and 2.38% experienced severe fatigue (Ihsan et al, 2021). A study in Iran that compared administrative department workers exposed to noise of 51.42 dB(A) (n = 26) and production department workers exposed to noise of 79.78 dB(A) (n = 26) showed significant differences in work fatigue using the Mann Whitney U Test (p = 0.000) (Heidari et al, 2021).…”
Section: Lactic Acid Level Measurementmentioning
confidence: 99%
“…29 Physical workload combined with noise intensity that exceeds 85 dB(A) for 8 hours of work could lead to fatigue symptomps such reduced concentration, physical exhaustion, dizziness and others. 30,31 Yovi et al 21 stated that noisy environmental conditions can cause the operator to feel tired and lose their concentration easily. Therefore, one strategy to control noise exposure is for the company to provide replacement workers when the noise exposure has exceeds the allowed time limit and provide them with the necessary PPE.…”
Section: Respondents' Concentration Level Assessmentmentioning
confidence: 99%